Investigating Indonesian EFL Students’ Responses of the Implementation of Intercultural Language Learning - Fauzi Miftakh (University of Kuningan, 2015)
This study aimed at discovering the students‟ responses to the implementation of intercultural language learning at the sixth semester students of the English Education Department, University of Singaperbangsa Karawang, Indonesia. The focus of the study was on 1) the students‟ general attitudes toward the course, 2) the students‟ attitudes toward the implementation of teaching and learning and 3) the students‟ responsibility as an intercultural person. This study was designed as a descriptive qualitative study that involved 31 participants. The data were collected through questionnaire and interviews. Based on the findings, the students gave positive responses to the implementation of intercultural language learning and they showed a greater interest in participating in the course. The intercultural language learning also proved that the students were given the opportunity to become intercultural speakers either during the teaching and learning process or in their daily life. Finally, it recommends that the intercultural approach should be implemented by other English teachers in any subject and at all levels of students.Keywords: interculural language learning, intercultural competence, English as a foreign language.